Violin Fingering: its Theory and Practice - Flesch, Carl 1873-1944; Schwarz, Boris 1906-1983; Menuhin, Yehudi 1916-1999 Sir; Flesch, Carl F. 1910-2008 (London Barrie & Rockliff, 1966)
This book was written during the last years of his life, and edited posthumously. In a very scientific and methodical manner, Carl Flesch takes us through 380 pages of musical examples from the violin literature offering multiple examples of each concept. Proper and well planned fingering choices are illustrated and then contrasted with the all too common poor, or sloppy fingering choices. In the mind of Flesch, fingering style is the bridge between the intentions of the composer and the interpretative genius of the performer. Once the concepts have been understood, internalized and mastered the violinist can then apply them to every piece they play resulting in cleaner playing style and less interference with the true character of the music due to technical limitations, thus affording the violinist more expressive power. It is not necessary for the reader to agree with every example in the book, as fingering style may be influenced by many factors. When the violinist can grasp the motivation for each fingering choice, they can then choose a fingering that works for them without violating the underlying concepts presented in this treatise.
Keywords: 20th Century (1901-2000); Violin; Method; Music education